Reasons for Outdoor Tanning in Adults: Q Methodology Identifies Three Types of Tanners - Ciara Bergmann; Tobias Konkel; Tatiana Görig; Esma Dursun; Katharina Diehl (Journal of Skin Cancer)
Discussion: These findings suggest that people may have different reasons for exposing themselves to harmful UV radiation, but that there is a pattern most participants in our study could be assigned to. Especially the finding that all groups tanned outdoors to meet their vitamin D needs seems to be a starting point for future research and skin cancer prevention.